Chromosomal location of a structural gene for the RNA polymerase sigma factor in Escherichia coli. - Nakamura, Y (1977)
A set of F' strains of Escherichia coli K-12 partially diploid for various chromosomal segments has been examined for possible gene dosage effects in the synthesis of sigma factor of the DNA-dependent RNA polymerase (RNA nucleotidyltransferase; nucleoside-triphosphate:RNA nucleoti-dyltransferase, EC 2.7.7.6). It was found that all F' strains diploid for the dnaG region synthesize sigma at rates two to three times higher than other F' or F- strains. Moreover, strains of Salmonella typhimurium harboring these F' plasmids produce E. coli sigma in addition to Salmonella sigma. This has been shown on the basis of the finding that Salmonella sigma can be precipitated with antiserum against E. coli RNA polymerase but is distinguishable from E. coli sigma in its mobility in sodium dodecyl sulfate/polyacrylamide gel electrophoresis. E. coli sigma polypeptides thus produced seem to be stable in cells of S. typhimurium. These results indicate that a structural gene for sigma (rpoD) is located at the metC-argG region, probably near the dnaG locus (66 min on the current genetic map of E. coli).